Green Sukuk As A Mechanism For Enhancing Green Islamic Finance -An Analytical Study Of The Green Sukuk Market During The Period (2017 - Third Quarter Of 2023)- (مجلة الواحات للبحوث والدراسات, 2025)
This research aims to identify the green sukuk and their role in green Islamic finance, then highlighting of the green sukuk market, based on the descriptive analytical approach. We concluded that this market has demonstrated remarkable growth, propelled by a rising interest from investors seeking sustainable and eco-friendly financial solutions. Despite a temporary downturn in 2020 and 2021, primarily due to the impacts of the COVID-19 pandemic on financial markets, the market exhibited a robust recovery, evidenced by a substantial uptick in activity from 2022 onwards. This resurgence underlines the pressing need for reforms within Islamic financial, which will further catalyze the advancement of green sukuk.Keywords: Green finance, Islamic finance, green Islamic finance, green sukuk